SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN PERAN GURU PAI DI SMP NEGERI 5 SEMPARUK TAHUN 2023-2024 - Teri Andrian; Aslan Aslan; Effiyadi Effiyadi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This thesis discusses the principal's supervision in improving the role of Islamic Religious Education teachers at SMP Negeri 5 Semparuk. This study has three research objectives, including the following; First, to determine the principal's supervision of the role of Islamic Religious Education teachers at SMP Negeri 5 Semparuk in improving Islamic Religious Education learning in 2023/2024. Second, to determine the role of the principal of SMP Negeri 5 Semparuk in improving Islamic Religious Education learning in 2023/2024. Third, to determine the implementation of Islamic Religious Education teachers at SMP Negeri 5 Semparuk in improving Islamic Religious Education learning. This type of research is qualitative research. There are three types of data collection techniques in this study, namely: Observation, Interviews, and Documentation. While the data analysis techniques used are data reduction, data presentation, verification and drawing conclusions. Then the data validity checking technique used is triangulation, triangulation and member check. The results of the study are: First, the principal's supervision of the role of Islamic Religious Education teachers at SMPN 5 Semparuk in improving Islamic Religious Education learning, namely in the following ways: 1) improving the facilities and infrastructure in the school so as to make teachers and students comfortable in carrying out the teaching and learning process so that the teaching and learning process can be more effective and efficient. 2) supervising the learning process during supervision so that it can improve teacher performance. Second, supervising the performance of teachers who are not good in carrying out the teaching and learning process and also providing input to teachers to improve teaching in delivering material to students. Third, 1) in implementing learning, Islamic Religious Education teachers use methods and approaches in the learning process so that the learning process will be effective. 2) after the learning process there will always be an evaluation to improve the understanding that students have received during the learning process